Optic pathway gliomas: a review. (March 2013) - Fried, Iris; Tabori, Uri; Tihan, Tarik; Reginald, Arun; Bouffet, Eric
SUMMARY Optic pathway gliomas account for 3–5% of all pediatric CNS tumors and represent the most common intrinsic optic nerve tumors. These tumors occur preferentially during the first decade of life and are particularly frequent in children with neurofibromatosis type 1. Although optic pathway gliomas are low-grade tumors, their behavior can be aggressive, and their management is often challenging. Their management includes observation, surgery, chemotherapy and radiation. The role of each modality is discussed as well as current and future developments in treatment, in particular targeted therapies that are currently being investigated.